Pembentukan Kader Muda Kesehatan Masyarakat dan Gizi di Panti Asuhan Muhammadiyah Tanah Abang I: The Establishment of Public Health and Nutrition Young Cadres at the Muhammadiyah Tanah Abang 1 Orphanage - Chica Riska Ashari; Ony Linda; Endang Listiowaty (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
One of the pillars of public health is nutrition which is an essential part of the growth and development of children. Nutrition has a close relationship with intelligence and health. Good and correct nutritional intake is needed so that children grow and develop optimally. This activity aims to form young community health and nutrition cadres at the Tanah Abang 1 Orphanage. The method used in this activity is the delivery of material, and then knowledge is measured before and after the children are given the material. The results of the Statistical Paired-Samples T-Test on the participants' pre and post-test results, the p-value was 0.005 (p-value <0.05), meaning that there was a significant difference between participants' knowledge before and after being given the material. In conclusion, this activity can increase knowledge about becoming a cadre of public health and nutrition.